CALCIUM OXIDE LEVELS IN SUGARCANE SILAGE, FRESH SUGARCANE OR CORN SILAGE FOR FEEDLOT NELLORE HEIFERS - K. A. K. Moraes1; S. C. Valadares Filho; E. H. B. K. Moraes; D. S. Pina (Journal of Animal and Plant Sciences, 2015)
The objective of this study was to evaluate intake, total apparent digestibility and performance of beef cattle fed different roughages: sugarcane silage with 0.0, 0.75 and 1.5% levels of calcium oxide, fresh sugarcane or corn silage. The roughages were corrected with urea/ammonium sulfate to have 10,5% of crude protein. Thirty Nellore heifers with average body weight 273.6 kg ± 25.72 kg, and 18 months were distributed in a completely randomized design. The animals, five per treatment, were confined in five collective stalls with troughs covered with asbestos shingles. The animals fed diets with corn silage showed higher DM intake than those fed the diets containing sugarcane silages and fresh sugarcane. Higher intakes of nutrient, except crude protein, were obtained with the diet containing fresh sugarcane as compared with the sugarcane silages. The total apparent digestibility of the nutrients was higher for the diet containing corn silage. Inclusion of calcium oxide had a quadratic effect on DM digestibility, with maximum digestibility estimated at the calcium oxide level of 0.82%. Corn silage-based diets yield higher performance than those containing sugarcane. Animals that fed diets containing fresh sugarcane had better performance than the animals fed sugarcane silage-based diets. The energy intake and performance of heifers fed diets based on corn silage are better than those of heifers fed sugarcane. The use of sugarcane silage without additives results in lower energy intake and lower performance. The calcium oxide level that resulted in best energy intake is close to 0.82%.
Keywords: intake; digestibility; performance